Mathematics Problem Solving Ability in Terms of Adversity Quotient in PBL Model with DAPIC Problem-Solving Process (Unnes Journal of Mathematics Education Research, 2022)
The study aims to describe the KPMM review of AQ on the PBL model with DAPIC problem-solving process of students in class VIII SMP Askhabul Kahfi Semarang. The descriptive qualitative method was chosen in this research, meanwhile, the researcher used a purposive sampling technique in taking the subject of research. There were six research subjects each consisting of two subjects on each AQ categorization. Research data was taken through an AQ questionnaire, TKPMM, interviews, and observation. The researcher used some techniques including reduction, presentation, then making a conclusion. TKPMM results showed that students in solving problems reviewed of AQ vary. Quitters’ students got quite a similar score, tend to give up easily, and were only capable to fulfil the first KPMM indicator. Campers’ students got various TKPMM scores, there was a student with high campers’ category but had equivalent TKPMM scores with quitters, chose to do what was necessary for the sake of aborting obligation, and earned score without giving more effort, were capably fulfilling two KPMM indicator. Student climbers got quite the same TKPMM score, earnest and maximizing capabilities, as well as capable to fulfil all KPMM indicators.